Responses of lowerbody power and match running demands after long-haul travel in international rugby sevens players - Mitchell, J. A.; Pumpa, K. L.; Pyne, D. B. (The Journal of Strength and Conditioning Research, 2017)
This study determined the effect of long-haul (>5 hours) travel on lower-body power and match running demands in international rugby sevens players. Lower-body power was assessed in 22 male international rugby sevens players (age 21.7 ± 2.7 years, mass 89.0 ± 6.7 kg, stature 180.5 ± 6.2 cm; mean ± SD) monitored over 17 rugby sevens tournaments. A countermovement jump was used to monitor lower-body power (peak and mean power) over repeated three week travel and competition periods (pretravel, posttravel, and posttournament). Small decreases were evident in peak power after both short and long-haul travel (-4.0%, ±3.2%; mean, ±90% confidence limits) with further reductions in peak and mean power posttournament (-4.5%, ±2.3% and -3.8%, ±1.5%) culminating in a moderate decrease in peak power overall (-7.4%, ±4.0%). A subset of 12 players (completing a minimum of 8 tournaments) had the effects of match running demands assessed with lower-body power. In this subset, long-haul travel elicited a large decrease in lower-body peak (-9.4%, ±3.5%) and mean power (-5.6%, ±2.9%) over the monitoring period, with a small decrease (-4.3%, ±3.0% and -2.2%, ±1.7%) posttravel and moderate decrease (-5.4%, ±2.5% and -3.5%, ±1.9%) posttournament, respectively. Match running demands were monitored through global positioning system. In long-haul tournaments, the 12 players covered ~13%, ±13% greater total distance (meter) and ~11%, ±10% higher average game meters >5 m/s when compared with short-haul (<5 hours) travel. Effective pretravel and posttravel player management strategies are indicated to reduce neuromuscular fatigue and running load demands in rugby sevens tournaments after long-haul travel.